A deformation separation method for gravity dam body and foundation based on the observed displacements. Issue 2 (3rd December 2018) - Lin, Chaoning; Li, Tongchun; Liu, Xiaoqing; Zhao, Lanhao; Chen, Siyu; Qi, Huijun
Summary: The displacement at arbitrary point in the dam is composed of two parts: One is the elastic deformation of dam body and the other that is due to the constrained deformation of foundation. The two parts should be separated to obtain reliable information reflecting the different characteristics of dam body and foundation. A simplified simulation method for gravity dam foundations is proposed that reflects the constrained deformation of foundation in a rational manner while taking into account the complex and diverse mechanical properties. Only the effects of the foundation on dam is investigated in the proposed model, and they are considered either centralized constraints or distributed constraints. The solution of the global foundation deformation is based on the monitoring displacements at measuring points in the gravity dam section using the hybrid partition finite element–interface boundary element approach. The reaction of the foundation on dam can be reflected by the global foundation deformation and the constrained force at dam bottom. On the basis, the whole dam response under a given load combination can be estimated using finite element theory. Three analyses have been performed on a typical gravity dam section to verify the feasibility of simplified simulations for different foundations as well as to allow for discussions regarding the differences among the simulations. An example analysis based on the proposed method is performed on a prototype gravity dam, and the results, which compared with actual measurements for discussions, show that the proposed method is reasonable and practical.